PENGEMBANGAN MEDIA PEMBELAJARAN FLIPBOOK PADA MATERI GERAK BENDA DI SMP - Desi Rahmawati; Sri Wahyuni; Yushardi Yushardi (JURNAL PEMBELAJARAN FISIKA, 2017)
This study was aimed at describing: (1) the expert validity of flipbook medialearning, (2) the users validity of flipbook media learning and (3) audience validityof flipbook media learning. This study was development research of 4-D method(define, design, develop, disseminate). The subjects of this study was students ofclass VIIIC Nuris junior high school Jember. The instruments used were sheet ofworksheet validation, sheet of student perfomance assement, sheet of studentresponse, and sheet of observstion. The result showed that: (1) expert validity offlipbook media learning was 86,47% with very valid category (2) user validity offlipbook media learning was 81,43% with valid category (3) audience validityvalidity of flipbook media learning was 90,39% with very valid, very effective,verycomplete, and can use without revision. Conclusion this reseach was flipbook medialearning on the material object motion in junior high school decent to be used as aphysics science of learning material in junior high school.Keywords : learning media, flipbook, motion